Preparation method of high-performance magnetoelectric synergistic gradient broadband metamaterial electromagnetic wave absorber
Patent Information
- Application Number
- CN202311426654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-10-31
AI Technical Summary
[0004]中国专利 CN110641130A公开了一种针对低频电磁波吸收的吸波泡沫的制备方法,其主要原料采用氧化石墨烯、多壁碳纳米管、羰基铁粉,并以聚氨酯软质泡沫为基体制备,目的是在保持吸波泡沫厚度薄,宽频吸收的前提下,重点解决吸波泡沫在L波段(1-2GHz)吸收性能不高的问题
1)强磁电协同损耗的设计有助于不同电磁波波段的有效损耗
Smart Images

Figure CN117594990B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave stealth technology, and specifically relates to a method for preparing a high-performance magnetoelectric synergistic gradient broadband metamaterial electromagnetic wave absorber, specifically a novel magnetic-dielectric synergistic absorbing metamaterial with ultra-wideband absorption capability of both high-frequency and low-frequency electromagnetic waves and its preparation method. Background Technology
[0002] With the widespread and rapid development of multi-band, broadband intelligent communication systems, electronic detection equipment, and synthetic aperture radar, electromagnetic pollution in space has caused numerous serious negative problems, including biological discomfort, electromagnetic interference, and information leakage. More importantly, the low-frequency bands of L (1-2 GHz) and S (2-4 GHz) are also widely used in 5G communication, long-range air-to-ground early warning radar, and meteorological detection due to their high transmission power. Therefore, exploring high-performance broadband electromagnetic wave absorbing materials capable of simultaneously covering low, medium, and high frequencies is of great significance in addressing the increasingly complex electromagnetic environment. Fundamentally, because higher loss capability implies poorer impedance matching, the core of achieving broadband electromagnetic wave absorption lies in resolving the contradiction between impedance matching across multiple frequency bands and the dissipation capability of high-intensity electromagnetic waves.
[0003] Generally, there are three main strategies for preparing high-performance broadband electromagnetic wave absorbing materials: multi-component composites with coupled magnetic and dielectric loss media, three-dimensional (3D) porous materials, and artificial metamaterials. For example, a Ti3C2Tx / Ni chain / ZnO array hybrid nanostructure exhibits an effective absorption bandwidth of 4.2 (8.2–12.4) GHz, graphene / Si3N4 shows an effective absorption bandwidth of 8 GHz, and a micron-sized Fe3O4-Fe3O4@C heterojunction composite material achieves 11.04 GHz@2 mm. Secondly, recent morphology-dependent studies have shown that porous framework structures are beneficial for suppressing the skin effect and enhancing multiple internal reflections and dissipation, such as reduced graphene oxide composite aerogels, porous carbon nanotube composites, and absorber-doped melamine foam. For example, an ultralight and highly compressible RGO foam was designed and managed to achieve multi-band absorption with an effective absorption bandwidth of 62.5 (4–18, 26.5–40, 75–110) GHz. Furthermore, the effective absorption bandwidth of magnetic ferrite-doped RGO foam can be extended to 3.4 GHz. These materials, relying on strong electrical losses accompanied by weak magnetic losses and micro / nano honeycomb structures, struggle to achieve effective absorption of electromagnetic waves in the low-frequency band. Third, artificial metamaterials with customized periodic arrangement units can achieve excellent impedance matching characteristics and enhance the attenuation capability of electromagnetic waves involving edge scattering and diffraction.
[0004] Chinese patent CN110641130A discloses a method for preparing absorbing foam for low-frequency electromagnetic wave absorption. The main raw materials used are graphene oxide, multi-walled carbon nanotubes, and carbonyl iron powder, with polyurethane flexible foam as the matrix. The aim is to address the problem of low absorption performance in the L-band (1-2 GHz) while maintaining a thin absorbing foam and wide-band absorption. However, this patent only provides reflection loss in the 1-4 GHz range, and the absorption performance shown in Figure 6 only achieves effective absorption exceeding -10 dB in the 2-3.25 GHz range, failing to cover the ultra-wideband electromagnetic wave absorption of 1-110 GHz.
[0005] To date, although various broadband electromagnetic wave absorbing materials have been reported, extending the effective absorption of low-frequency bands (especially the L-band) while ensuring effective absorption of broadband electromagnetic waves remains a significant challenge. This invention proposes a synergistic loss mechanism of magnetic dielectric loss and, combined with metamaterial structure design, optimizes impedance matching while introducing structural loss capability, thus solving the problem that broadband electromagnetic wave absorbing materials cannot cover low-frequency electromagnetic waves. Summary of the Invention
[0006] The technical problem to be solved by this invention is to propose a high-performance magnetoelectric synergistic gradient broadband metamaterial that addresses the shortcomings of the aforementioned broadband absorbing materials. This metamaterial possesses an effective wide absorption frequency band and also absorbs low-frequency electromagnetic waves.
[0007] The technical solution of this invention to solve its technical problem is that the electromagnetic wave absorber of the ultra-wideband electromagnetic wave absorbing material is divided into upper and lower units. The top is an array composed of lightweight porous graphene-based aerogel material, which can minimize the interface reflection of electromagnetic waves and has excellent dielectric loss performance and impedance matching properties. The bottom is a resin film filled with oriented carbonyl iron, which has high permeability and strong magnetic loss capability.
[0008] The present invention provides a method for fabricating a high-performance magnetoelectric synergistic gradient broadband metamaterial electromagnetic wave absorber, mainly consisting of two parts. The graphene-based aerogel preparation method involves: uniformly mixing an aqueous solution of graphene oxide, carbon nanotubes, and cellulose (these three materials have abundant oxygen-containing functional groups on their surfaces, which can form a uniform and stable colloidal solution, ensuring that the prepared aerogel has abundant specific area and heterogeneous interface); then forming a three-dimensional network structure using a directional freezing method. The macroscopic structure of the aerogel depends on the 3D-printed resin-based template. After annealing and reduction under an inert gas, the graphene-based aerogel is obtained. A highly oriented carbonyl iron resin-based magnetic film is prepared using a shear orientation method. Specific steps include: 1) Mix the aqueous dispersions of graphene oxide, carbon nanotubes and nanocellulose in proportion and stir vigorously to obtain a mixed colloidal solution of graphene, carbon nanotubes and nanocellulose.
[0009] 2) By using a directional freezing method, a colloidal solution of graphene oxide, carbon nanotubes and nanocellulose is placed in a 3D-printed resin-based template. The template is placed on a low-temperature freezing plate for freezing treatment, which transforms it from a liquid state to a solid state. The template is then freeze-dried at a gradient freezing temperature of -80℃ to 5℃ for 48-168 h to obtain porous graphene oxide, carbon nanotubes and nanocellulose composite aerogels with different geometries.
[0010] 3) In an inert atmosphere, the obtained graphene oxide, carbon nanotubes, and nanocellulose aerogel are annealed and reduced at a temperature of 200-800 °C to obtain reduced porous graphene, carbon nanotubes, and cellulose carbon aerogel (aerogel material). Preferably, the annealing temperature is 300 °C.
[0011] 4) Weigh out flake carbonyl iron powder and mix it with (poly)acrylic resin (75000~120000). Mix thoroughly in a stirrer at a speed of 10-500 rpm to obtain a fluid magnetic powder (poly)acrylic resin-based viscous substance (magnetic viscous substance).
[0012] 5) Pour the magnetic viscous material onto a polytetrafluoroethylene vinyl plate and use a scraper with a height of 10-500 μm to uniformly coat the magnetic viscous material to obtain sheet-like carbonyl iron resin films of different thicknesses with horizontal orientation.
[0013] 6) After drying at room temperature for 12-24 h to remove the solvent, an oriented sheet-like carbonyl iron composite magnetic film is obtained.
[0014] 7) Assemble the obtained aerogel material with a magnetic film. Arrange graphene / carbon nanotube / cellulose aerogels into an array and cover the bottom with a sheet-like carbonyl iron resin film to obtain a high-performance magnetoelectric synergistic gradient broadband metamaterial with strong dielectric loss and strong magnetic loss. Step 1) The concentration of the aqueous dispersion of graphene oxide, carbon nanotubes, and nanocellulose is 3-15 mg / mL, and the mass ratio of graphene oxide:carbon nanotubes:nanocellulose is [missing information]. 6:6:1-2:2:1 Preferably, the mass ratio of graphene oxide, carbon nanotubes, and cellulose is 3:2:1.
[0015] The freeze-drying temperature gradient in step 2) is as follows: drying at -30℃ for 24 h; drying at -20℃ for 12-24 h; drying at -10℃ for 12-24 h; drying at 0℃ for 12-24 h; drying at 5℃ for 12-72 h; and the vacuum degree is 0.1-1.0.
[0016] Preferably, a gradient freeze-drying method is used, with the following temperature gradients: drying at -30℃ for 24 h; drying at -20℃ for 24 h; drying at -10℃ for 24 h; drying at 0℃ for 24 h; and drying at 5℃ for 72 h. More preferably, the freeze-drying temperature is -20℃ and the freeze-drying time is 160 h.
[0017] Step 3) uses argon or nitrogen as the inert atmosphere, the reaction temperature is 200-800 ℃, and the reaction time is 2-4 h. Preferably, the annealing and reduction temperature is 300 ℃ for 3 h, and the heating rate is 5 ℃ per minute.
[0018] Step 2) The composite aerogel has the following structural shapes: cube, cuboid, cylinder, frustum, prism, frustum or polyhedron.
[0019] The spherical carbonyl iron in step 3) has a size of 1-10 μm.
[0020] In step 4), the mass fraction of the flake carbonyl iron powder in the resin-based magnetic slurry is 10%-90%. Preferably, the mass ratio of the magnetic powder to the resin material in step 4) is 3:2; and the stirring and degassing speed is 400 rpm.
[0021] The scraper height mentioned in step 5) is 50 μm.
[0022] The drying time in step 6) is 12 hours.
[0023] Step 7) describes an aerogel array structural unit as a decapod; the thickness of the oriented sheet-like carbonyl iron composite magnetic film is 1.5 mm. The mass ratio of graphene oxide to carbonyl iron is 1:20~60.
[0024] This invention provides a method for preparing a magnetoelectric synergistic gradient broadband metamaterial, resulting in an ultra-wideband absorbing material that combines low and high frequencies.
[0025] The innovative strategy provided by this invention offers insights into the manufacture of high-performance, multi-band, ultra-wideband electromagnetic wave absorbing materials with low-frequency compatibility.
[0026] This invention provides a method for preparing high-performance magnetoelectric synergistic gradient broadband metamaterials, which can effectively cover broadband absorption of both low and high frequencies. As a typical dielectric loss material, graphene-based aerogel arrays ensure high-frequency electromagnetic wave loss and optimize impedance matching, while oriented sheet-like carbonyl ferromagnetic films with high permeability and strong magnetic loss capability ensure efficient attenuation of low-frequency electromagnetic waves penetrating to the bottom layer.
[0027] The metamaterials of this invention, possessing ultra-wideband electromagnetic wave absorption properties, have significant application value in complex electromagnetic environments. The high-performance magnetoelectric synergistic gradient metamaterial electromagnetic wave absorber prepared by this invention exhibits excellent broadband absorption properties, simultaneously covering low-frequency, mid-frequency, and high-frequency electromagnetic waves, while also possessing excellent average absorption intensity.
[0028] Compared to the prior art document CN110641130A, the difference of this invention is that the prior art document uses an absorber-filled polymer resin to obtain porous microwave absorbing materials, while this invention uses a three-dimensional network structure formed by the cross-linking of two-dimensional graphene sheets, carbon nanotubes, and cellulose. Although the prior art document also uses graphene and carbonyl iron powder, it merely physically mixes the two, resulting in a relatively weak magnetic-dielectric synergistic effect. Many iterations are needed to obtain suitable electromagnetic properties, and it is difficult to fully utilize the strong dielectric and magnetic losses of both materials. This invention arranges the array of strong dielectric materials and the strong magnetic absorbing materials in a gradient manner, so that each unit can effectively absorb electromagnetic waves in its corresponding frequency band. This magnetic-dielectric synergistic effect is greatly enhanced compared to the prior art document. It is precisely the design of varying the quantities of graphene, carbon nanotubes, and nanocellulose used in this invention, along with the specific amount of carbonyl iron, that produces a more positive synergistic combination and enhanced technical effect, namely, the key solution to the significant improvement in absorption performance caused by the design of gradient metamaterials.
[0029] Compared with the prior art, the present invention has the following advantages: 1) The design of strong magnetoelectric co-loss contributes to the effective loss of different electromagnetic wave bands. 2) Metamaterial structure design helps to achieve impedance matching of electromagnetic waves across the entire wavelength range. 3) The effective absorption bandwidth of the magnetoelectric synergistic gradient metamaterial can cover 1-40 and 50-110 GHz. 4) The magnetoelectric co-gradient metamaterial achieved an average absorption intensity of -19.3 dB in the tested frequency band. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the structure of the magnetoelectric synergistic metamaterial of the present invention.
[0031] Figure 2 This is a scanning electron microscope (SEM) image of the oriented aerogel material in Example 1.
[0032] Figure 3 This is a scanning electron microscope (SEM) image of the oriented sheet-like carbonyl iron resin film in Example 1.
[0033] Figure 4The image shows the broadband absorption performance test results of the magnetoelectric synergistic metamaterial in Example 1 (reflectivity curves in the frequency ranges of 1-40 GHz and 50-100 GHz).
[0034] Figure 5 A comparison of the absorption properties of three different materials. Implementation
[0035] The present invention will now be described in detail with reference to specific embodiments and accompanying drawings. These embodiments are only intended to help those skilled in the art better understand the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention.
[0036] Unless otherwise specified, the experimental methods used in the examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available. The reflectivity of the high-performance magnetoelectric synergistic gradient broadband metamaterial electromagnetic wave absorber was tested using the arch method in GJB 5239-2004, with test frequencies of 1-40 GHz and 50-110 GHz. Example
[0037] The specific fabrication steps of a high-performance magnetoelectric synergistic gradient broadband metamaterial are as follows: 1) Take 30, 20, and 10 mL of aqueous dispersions of graphene oxide, carbon nanotubes (Kenye Technology, diameter 10-20 nm, length 20-40 μm) and nanocellulose (SanDisk Technology, diameter 5-30 nm, length 40-100 μm) respectively and add them to a glass container. Stir vigorously with a paddle. The concentration of the dispersion is 5 mg / mL to obtain a mixed colloidal solution of graphene oxide / carbon nanotubes / nanocellulose.
[0038] 2) Pour the above mixed colloidal solution into a pre-printed resin template (3D printed resin-based template). The template is in the shape of a truncated pyramid and is placed on a low-temperature freezing plate for freezing treatment at a temperature of -30°C.
[0039] 3) Once the mixed colloidal solution is completely frozen into a solid state, transfer it to a freeze dryer and remove ice crystals using a gradient freeze-drying method. The temperature gradient is: -30℃ (24 h), -20℃ (24 h), -10℃ (24 h), 0℃ (24 h), 5℃ (72 h).
[0040] 4) In argon atmosphere, the freeze-dried graphene oxide / carbon nanotube / cellulose aerogel was placed in a tube furnace and calcined at 300°C for 3 hours, with a heating rate of 5°C per minute, to obtain vertically oriented graphene / carbon nanotube / cellulose aerogel. Figure 1(It) has a shape that is a quadrangular frustum.
[0041] 5) Take 10 g of spherical carbonyl iron powder (1-10 μm) and 100 mL of anhydrous ethanol solution (99.5%) and add them to a spherical ball mill jar. The mass ratio of the milling beads to the carbonyl iron powder is 20:1. The milling speed is 400 rpm and the milling time is 12 h to obtain flake carbonyl iron powder.
[0042] 6) Carbonyl iron powder and acrylic resin (75,000 to 120,000, take the single value) are mixed evenly in a degassing machine at a mass ratio of 7:3 to obtain carbonyl iron / acrylic resin composite slurry. The slurry is poured onto a polytetrafluoroethylene vinyl plate and coated with a doctor blade with a height of 200 μm to obtain a horizontally oriented sheet-like carbonyl iron resin film. Figure 2 The dimensions are 300×300 mm. 2 .
[0043] 7) Arrange graphene / carbon nanotubes / cellulose aerogels into an array ( Figure 1 A high-performance magnetoelectric synergistic gradient broadband metamaterial (300×300 mm) is composed of a sheet-like carbonyl iron resin film covering the bottom. 2 ).
[0044] Testing: The reflectivity of the obtained high-performance magnetoelectric synergistic gradient broadband metamaterial was tested in the microwave bands of 1-40 GHz and 50-110 GHz (arch method).
[0045] First, the vector network analyzer (Agilent, N5230) connected to the bow-shaped frame was calibrated. After calibration, the absorbing sample to be tested was placed on a standard aluminum reflector for absorption and reflectivity measurement. The sample size was 300 × 300 mm. 2 The test results are as follows: Figure 4 As shown, in all test frequency bands, the effective absorption bandwidth of the high-performance magnetoelectric synergistic gradient broadband metamaterial can cover 1-40 GHz and 50-100 GHz. It is the widest absorbing material in the microwave band. While ensuring wideband effective absorption, the average absorption rate reaches -19.3 dB, which can effectively dissipate 98.8% of electromagnetic waves. Example
[0046] The specific fabrication steps of a high-performance magnetoelectric synergistic gradient broadband metamaterial are as follows: 1) Take 30, 30, and 10 mL of aqueous dispersions of graphene oxide, carbon nanotubes, and cellulose respectively and add them to glass containers. Stir vigorously with a stirring paddle to obtain a mixed colloidal solution of graphene oxide / carbon nanotubes / cellulose at a concentration of 6 mg / mL.
[0047] 2) Pour the above mixed colloidal solution into a pre-printed resin template, which is in the shape of a decagonal truncated pyramid, and place it on a low-temperature freezing plate for freezing treatment at a temperature of -40 ℃.
[0048] 3) Once the mixed colloidal solution is completely frozen into a solid state, transfer it to a freeze dryer and remove ice crystals using a gradient freeze-drying method. The temperature gradient is -30℃ (24 h), -20℃ (24 h), -10℃ (24 h), 0℃ (24 h), and 5℃ (72 h). 4) In argon atmosphere, the freeze-dried graphene oxide / carbon nanotube / cellulose aerogel was placed in a tube furnace and calcined at 500 °C for 2 h with a heating rate of 5 °C per minute to obtain graphene / carbon nanotube / cellulose aerogel in the shape of a deca-faceted truncated pyramid.
[0049] 5) Take 20 g of spherical carbonyl iron powder and 100 mL of ethanol solution and add them to a spherical ball mill jar. The mass ratio of the milling beads to the carbonyl iron powder is 20:1. The milling speed is 400 rpm and the milling time is 18 h to obtain flake carbonyl iron powder.
[0050] 6) Carbonyl iron powder and acrylic resin are mixed evenly in a degassing machine at a mass ratio of 8:2 to obtain a carbonyl iron / acrylic resin composite slurry. This slurry is then poured onto a polytetrafluoroethylene (PTFE) vinyl ester substrate and coated using a 100 μm high doctor blade to obtain a horizontally oriented sheet-like carbonyl iron resin film. (300×300 mm) 2 .
[0051] 7) A high-performance magnetoelectric synergistic gradient broadband metamaterial is constructed by arranging graphene / carbon nanotubes / cellulose aerogels in an array and covering the bottom with a sheet-like carbonyl iron resin film. (300×300 mm) 2 .
[0052] 8) The reflectivity of the obtained high-performance magnetoelectric synergistic gradient broadband metamaterial was tested in the microwave bands of 1-40 GHz and 50-110 GHz (arch method). In all test bands, the high-performance magnetoelectric synergistic gradient broadband metamaterial achieved an absorptivity of -10 dB, an effective absorption bandwidth of 78 GHz, and an average absorption intensity of -15.4 dB.
[0053] The testing method is the same as in Example 1. Example
[0054] The specific fabrication steps of a high-performance magnetoelectric synergistic gradient broadband metamaterial are as follows: 1) Take 60, 30, and 10 mL of aqueous dispersions of graphene oxide, carbon nanotubes, and cellulose respectively and add them to glass containers. Stir vigorously with a paddle until the concentration is 15 mg / mL to obtain a mixed colloidal solution of graphene oxide / carbon nanotubes / cellulose.
[0055] 2) Pour the above mixed colloidal solution into a pre-printed resin template, which is shaped like a frustum, and place it on a low-temperature freezing plate for freezing treatment at a temperature of -30 ℃.
[0056] 3) Once the mixed colloidal solution is completely frozen into a solid state, transfer it to a freeze dryer and remove ice crystals using a gradient freeze-drying method. The temperature gradient is -30 ℃ (24 h), -20 ℃ (24 h), -10 ℃ (24 h), 0 ℃ (24 h), and 5 ℃ (72 h).
[0057] 4) In argon atmosphere, the freeze-dried graphene oxide / carbon nanotube / cellulose aerogel was placed in a tube furnace and calcined at 400 °C for 2 h with a heating rate of 5 °C per minute to obtain graphene / carbon nanotube / cellulose aerogel in the shape of a frustum.
[0058] 5) Take 20 g of spherical carbonyl iron powder and 100 mL of ethanol solution and add them to a spherical ball mill jar. The mass ratio of the milling beads to the carbonyl iron powder is 20:1. The milling speed is 400 rpm and the milling time is 18 h to obtain flake carbonyl iron powder.
[0059] 6) Carbonyl iron powder and acrylic resin are mixed evenly in a degassing machine at a mass ratio of 7:3 to obtain a carbonyl iron / acrylic resin composite slurry. This slurry is then poured onto a polytetrafluoroethylene (PTFE) vinyl ester substrate and coated using a doctor blade with a height of 300 μm to obtain a horizontally oriented sheet-like carbonyl iron resin film. (300×300 mm) 2 .
[0060] 7) A high-performance magnetoelectric synergistic gradient broadband metamaterial is constructed by arranging graphene / carbon nanotubes / cellulose aerogels in an array and covering the bottom with a sheet-like carbonyl iron resin film. (300×300 mm) 2 .
[0061] 8) The reflectivity of the obtained high-performance magnetoelectric synergistic gradient broadband metamaterial was tested in the microwave bands of 1-40 GHz and 50-110 GHz (arch method). In all test bands, the high-performance magnetoelectric synergistic gradient broadband metamaterial achieved an absorptivity of -10 dB, an effective absorption bandwidth of 88 GHz, and an average absorption intensity of -14.4 dB.
[0062] The testing method is the same as in Example 1.
[0063] Comparative example A separate sheet-like carbonyl iron-filled polyacrylic acid resin film was prepared according to the operating steps and process conditions given in Example 1. The film is named "Sheet-like Carbonyl Iron-filled (Poly)acrylic Acid Resin Film (Separate Magnetic Film Material)" and has a size of 30 × 30 mm. 2; Following the operating steps and process conditions given in Example 1, a separate dielectric metamaterial (single dielectric material), namely an array of aerogel materials, was prepared. This array, named Aerogel Array Metamaterial, measures 300 × 300 mm. 2 .
[0064] Individual magnetic film materials and individual dielectric materials were tested and compared with the magnetoelectric metamaterial prepared in Example 1. Figure 5 As shown, a comparison of the absorption performance of three different materials reveals that the absorption performance of individual magnetic films and dielectric metamaterials is poor in the low-frequency 1-6 GHz band. This is because a single loss mechanism is insufficient to address the poor absorption of broadband electromagnetic wave absorbing materials in the low-frequency band. However, by adopting the magnetic-dielectric synergistic metamaterial design scheme proposed in this invention, the broadband electromagnetic wave absorption bandwidth can be further extended to the low-frequency band, successfully achieving broadband effective absorption covering both low-frequency and high-frequency bands.
Claims
1. A method for fabricating a high-performance magnetoelectric synergistic gradient metamaterial electromagnetic wave absorber, characterized in that: The steps included are: 1) Mix the aqueous dispersions of graphene oxide, carbon nanotubes and nanocellulose in proportion and stir vigorously to obtain a mixed colloidal solution of graphene, carbon nanotubes and nanocellulose. 2) By using a directional freezing method, a colloidal solution of graphene oxide, carbon nanotubes and nanocellulose is placed in a 3D printed resin-based template. The template is placed on a low-temperature freezing plate for freezing treatment, which transforms it from a liquid state to a solid state. The template is then freeze-dried at -80 to 5℃ for 48 to 168 hours to obtain a porous composite aerogel with different geometric shapes formed by graphene oxide, carbon nanotubes and nanocellulose. 3) In an inert atmosphere, the obtained graphene oxide, carbon nanotubes and nanocellulose aerogels are annealed and reduced at a temperature of 200-800℃ for 2-4 hours to obtain a reduced porous graphene / carbon nanotube / cellulose aerogel material. 4) The flake carbonyl iron powder newly prepared from spherical carbonyl iron powder is mixed with (poly)acrylic resin and thoroughly mixed in a stirrer at a speed of 10-500 rpm to obtain a fluid magnetic powder, namely (poly)acrylic resin-based magnetic viscous material. 5) Pour the magnetic viscous material onto a polytetrafluoroethylene vinyl plate and use a scraper with a height of 10-500μm to uniformly coat the magnetic viscous material to obtain sheet-like carbonyl iron resin films of different thicknesses with horizontal orientation. 6) After drying at room temperature for 12-24 hours to remove the solvent, an oriented sheet-like carbonyl iron composite magnetic film is obtained; 7) Assemble the obtained aerogel material with the composite magnetic film, arrange the graphene / carbon nanotube / cellulose aerogel into an array, and cover the bottom with a sheet-like carbonyl iron resin film to obtain a high-performance magnetoelectric synergistic gradient broadband metamaterial electromagnetic wave absorber with strong dielectric loss and strong magnetic loss synergistic. The concentration of the aqueous dispersion of graphene oxide, carbon nanotubes and nanocellulose is 3-15 mg / mL; the mass ratio of graphene oxide:carbon nanotubes:nanocellulose is 6:6:1-2:2:
1.
2. The preparation method according to claim 1, characterized in that: The concentration of the aqueous dispersion of graphene oxide, carbon nanotubes and nanocellulose in step 1) is 5 mg / mL; the mass ratio of graphene oxide, carbon nanotubes and cellulose is 3:2:
1.
3. The preparation method according to claim 1, characterized in that: The freezing treatment gradient in step 2) is as follows: drying at -30℃ for 24 hours; drying at -20℃ for 12-24 hours; drying at -10℃ for 12-24 hours; drying at 0℃ for 12-24 hours; drying at 5℃ for 12-72 hours; with a vacuum degree of 0.1-1.
0.
4. The preparation method according to claim 1, characterized in that: Step 2) describes the following freezing treatment gradients: drying at -30℃ for 24 hours; drying at -20℃ for 24 hours; drying at -10℃ for 24 hours; drying at 0℃ for 24 hours; and drying at 5℃ for 72 hours.
5. The preparation method according to claim 1, characterized in that: The freezing temperature in step 2) is -20℃, and the freeze-drying time is 160h.
6. The preparation method according to claim 1, characterized in that: Step 3) The inert atmosphere is argon and nitrogen; the graphene oxide, carbon nanotubes and nanocellulose aerogel are annealed and reduced at 300°C for 3 hours; the heating rate is 5°C per minute.
7. The preparation method according to claim 1, characterized in that: Step 2) The composite aerogel has the following structural shapes: cube, cuboid, cylinder, frustum, prism, frustum or polyhedron.
8. The preparation method according to claim 1, characterized in that: The spherical carbonyl iron in step 4) has a size of 1-10 μm; the mass fraction of the flake carbonyl iron powder in the resin-based magnetic slurry is 10%-90%; the mass ratio of the magnetic powder to the resin material in step 4) is 3:2; the rotation speed in the stirring degassing machine is 400 rpm; the mass ratio of graphene oxide to carbonyl iron is 1:20-60.
9. The preparation method according to claim 1, characterized in that: In step 5), a magnetic viscous material is uniformly coated using a scraper with a height of 50 μm; in step 6), after drying at room temperature for 12 h to remove the solvent, an oriented sheet-like carbonyl iron composite magnetic film is obtained.
10. The preparation method according to claim 1, characterized in that: The structural unit of the graphene / carbon nanotube / cellulose aerogel arranged in an array in step 7) is a deca-shaped truncated pyramid.
11. The preparation method according to claim 9, characterized in that: The thickness of the oriented sheet-like carbonyl iron composite magnetic film is 1.5 mm.
12. A broadband metamaterial electromagnetic wave absorber prepared by any of the preparation methods described in claims 1-11.
Citation Information
Patent Citations
Preparation method of wave-absorbing foam for absorbing low-frequency electromagnetic waves
CN110641130A
Preparation method of graphene-enhanced biomass porous carbon electromagnetic wave-absorbing material
AU2020102003A4
Graphene compounded wave absorbing material and preparation method thereof
CN106479433A